Correlations between tensiomyography variables and lower extremity power - Tabakovic, A.; Abazovic, E.; Tabakovic, M.; Kovacevic, E. (Baltic Journal of Health and Physical Activity, 2024)
Introduction: The main aim of this research was to determine whether there are statistically significant correlations between TMG variables and jumping performance.